PONDERACIÓN DE LOS PROMEDIOS DEL COLEGIO EN LA ADMISIÓN-UNI - Ordoñez Mercado, Alipio (1999)
The allocation appropriate weights problem to academic performance in high school for the National Engineering University’s postulant is considered. The constant mean linear model with two restriction and ten admission exam data between 1995 to 1999 are used to perform the objective. The statistics analysis suggests that adequate choices are 0.94 to admission exam and 0.06 to high school averages.